Design and Development of Internal Pipe Inspection Robot - Rushikesh Kokane; Chintamani R Upadhye; Bhushan S Kumbhar (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
In this modern era, the robotics has become the most significant key in almost all working fields of engineering where work is done without or with minimal physical interference of humans. In the field of engineering the robots are being used to reduce the work effort, to ease the work, to do the work in the areas where humans are inaccessible, to give precision in work, etc. In essence, robots are utilized to boost performance and efficiency while reducing manufacturing costs. The most reliable and secure method of transferring liquid and gas is through a pipeline. Robots have already taken over the production sector in the pipeline industries, they are also utilized in the inspection sector. Since the majority of the fluids that are delivered from pipes are toxic and hazardous, direct human contact is prohibited in this inspection area. The defects occurs external areas of pipe can be easily noticeable and fixable, but those that arise inside the pipe are more difficult to detect and more challenging to fix. So the internal pipe inspection robots are designed to ease the inspection for internal area of pipeline. These robots are designed to move inside the narrow area of pipe to detect, locate and fix the defect. The main objective of current work is to reduce the human effort and provide safety in pipeline inspection sector. This robot can move along the various diameters pipes within its prescribed range. With the help of DC motor the forward and reverse movement is obtained, while IR sensors and camera used to detect the defects like blockage, holes or cracks, dents, leakages, etc. How to cite this article: Kokane RS, Upadhye CR, Kumbhar BS. Design and Development of Internal Pipe Inspection Robot. J Adv Res Mech Engi Tech 2022; 9(3&4): 6-11. DOI: https://doi.org/10.24321/2454.8650.202202